Buy ology : truth and lies about why we buy - Lindstrom, Martin, 1970- (New York : Doubleday, 2008)
How much do we know about why we buy? What truly influences our decisions in today's message-cluttered world? An eye-grabbing advertisement, a catchy slogan, an infectious jingle? Or do our buying decisions take place below the surface, so deep within our subconscious minds that we're barely aware of them? Marketing guru Lindstrom presents the startling findings from his three-year, seven-million-dollar neuromarketing study, a cutting-edge experiment that peered inside the brains of 2,000 volunteers from all around the world as they encountered various ads, logos, commercials, brands, and products. His startling results shatter much of what we have long believed about what seduces our interest and drives us to buy.--From publisher description.
Includes bibliographical references (p. 217-229) and index.
Keywords: Neuromarketing; Consumer behavior -- Psychological aspects; Shopping -- psychological aspects; Marketing -- Psychological aspects